2021
DOI: 10.3390/life11030197
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of EGCG, a Green Tea Polyphenol, for Treatment of Coronavirus Diseases

Abstract: Epigallocatechin gallate (EGCG) is a major catechin found in green tea, and there is mounting evidence that EGCG is potentially useful for the treatment of coronavirus diseases, including coronavirus disease 2019 (COVID-19). Coronaviruses encode polyproteins that are cleaved by 3CL protease (the main protease) for maturation. Therefore, 3CL protease is regarded as the main target of antivirals against coronaviruses. EGCG is a major constituent of brewed green tea, and several studies have reported that EGCG in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 73 publications
3
40
0
Order By: Relevance
“…Among the catechins discussed, ECGC is a very promising nephroprotective and anti-SARS-CoV-2 compound, especially due to the antiviral activities discussed earlier in this review [ 67 , 68 , 69 ]. Together, the experimental and clinical data in the present review support the indication of catechins as promising molecules in the treatment of COVID-19-associated AKI [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]. In addition, catechins can also be used as a prototype for the synthesis of more active analogs for the treatment of AKI.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Among the catechins discussed, ECGC is a very promising nephroprotective and anti-SARS-CoV-2 compound, especially due to the antiviral activities discussed earlier in this review [ 67 , 68 , 69 ]. Together, the experimental and clinical data in the present review support the indication of catechins as promising molecules in the treatment of COVID-19-associated AKI [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]. In addition, catechins can also be used as a prototype for the synthesis of more active analogs for the treatment of AKI.…”
Section: Discussionsupporting
confidence: 72%
“…However, there was no significant effect of EGCG on renal blood flow, GFR, urine volume and urinary sodium excretion [ 86 ]. Considering the severity and the timeline of AKI onset induced by the UUO model, we believe that the use of higher doses of EGCG could have a more profound therapeutic effect [ 97 , 98 ].…”
Section: Reno-protective Effect Of Catechins In the Acute Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of data suggests that the preventive activity is due to EGCG interference with the interactions between SARS-CoV-2 and angiotensin converting enzyme 2 (ACE2) [ 2 , 7 , 8 ]. This is attributable to EGCG binding with spike (S) protein [ 10 ]. However, alternatives, such as EGCG interactions with the cell surface receptors or EGCG-induced alterations of membrane fluidity [ 11 ], have not been tested properly with the live virus.…”
Section: Resultsmentioning
confidence: 99%
“…Despite several limitations, the findings of present study might help to elucidate on the mechanisms of action of the anti-viral effects of catechins in the oral cavity. Recent studies reported an inhibitory effect of EGCG on COVID-19, which has increased attention toward green tea as a non-pharmacological preventive measure [ 19 , 20 , 21 ]. Although there are still many unknowns regarding the clinical effects of catechins in humans, we believe that the results of this study will guide future research related to catechins and contribute to their further development toward enhancing human health.…”
Section: Discussionmentioning
confidence: 99%